Left ventricular non-compaction cardiomyopathy mimicking an infiltrative cardiac disease - Buß, Sebastian Johannes; Mereles, Derliz; Katus, Hugo; Hardt, Stefan (International journal of cardiology, 2011)
A 60-year-old male patient, with coronary artery bypass graft due to coronary artery disease 9 years ago, without a history of prior myocardial infarction, was referred to our clinic for further cardiologic evaluation. Routine transthoracic echocardiography showed a slightly reduced left ventricular function with a massive left ventricular hypertrophy located mainly to the anterolateral and inferolateral segments, including basal segments and papillary muscles, mimicking a myocardial infiltrative disease, e.g. cardiac amyloidosis. Echocardiographic criteria for left ventricular non-compaction cardiomyopathy (LVNC) were not fulfilled. For further evaluation of the unusual asymmetric wall thickening, an echocardiographic examination with a left heart contrast agent was conducted. Deep intertrabecular recesses of the anterolateral and inferolateral segments could now be unmasked. Left ventricular hypertrabeculation-noncompaction represents rare abnormalities, diagnosed when many left ventricular trabeculations are visibly apical to the papillary muscles and intertrabecular spaces are perfused from the ventricular cavity. To our knowledge, this is the first report of a patient with LVNC mimicking an infiltrative myocardial disease in echocardiography. This case represents a possible pitfall in the diagnosis of LVNC, which could sometimes be avoided by using LV opacification agents.
Available online 20 February 2009
Gesehen am 27.06.2022